1977
DOI: 10.1042/bj1670685
|View full text |Cite
|
Sign up to set email alerts
|

Fungal degradation of aromatic nitriles. Enzymology of C-N cleavage by Fusarium solani

Abstract: 1. A strain of the fungus Fusarium solani able to use benzonitrile as sole source of carbon and nitrogen was isolated by elective culture. 2. Respiration studies indicate that the nitrile, after degradation to benzoate, is catabolized via catechol or alternatively via p-hydroxybenzoate and 3,4-dihydroxybenzoate. 3. Cell-free extracts of benzonitrile-grown cells contain an enzyme mediating the conversion of benzonitrile into benzoate and ammonia. 4. The nitrilase enzyme was purified by DEAE-cellulose chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 15 publications
0
62
1
Order By: Relevance
“…Cloning of the gene locus (bxn) encoding the bromoxynilspecific nitrilase will facilitate comparison at the gene level of this enzyme to nitrilases identified in other organisms (4,17,18). The bxn gene is also being tailored for expression in plants to confer a bromoxynil-resistant phenotype to bromoxynil-sensitive crops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning of the gene locus (bxn) encoding the bromoxynilspecific nitrilase will facilitate comparison at the gene level of this enzyme to nitrilases identified in other organisms (4,17,18). The bxn gene is also being tailored for expression in plants to confer a bromoxynil-resistant phenotype to bromoxynil-sensitive crops.…”
Section: Discussionmentioning
confidence: 99%
“…A number of soil microbes that are capable of utilizing benzonitrile or 4-hydroxybenzonitrile as a sole source of carbon, nitrogen, or both have been identified (4,17,18). These organisms contain an enzyme, termed nitrilase, that converts benzonitrile and related compounds to their corresponding benzoic acid derivatives, releasing ammonia as a by-product (4,17,18). These nitrilases, however, cannot catalyze the conversion of bromoxynil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also the nitrilases from Rhodococcus rhodochrous NCIMB 11215, R. rhodochrous NCIMB 11216, Fusarium species and Arthrobacter sp. strain J1 were rapidly inactivated during storage (Bandyopadhyay et al, 1986;Harper, 1976Harper, , 1977Harper, , 1985Goldlust & Bohak 1989). Several investigators have added reducing agents such as DTT to the enzyme preparations in order to prevent oxidation of the thiol residues which are supposed to be involved in the hydrolysing reaction (Kobayashi et al, 1992;Nagasawa et al, 1990).…”
mentioning
confidence: 99%
“…Cain et al reported a Fusarium oxysporum strain that did not grow on salicylate but grew well on catechol (9). Catechol and gentisate are intermediates in other catabolic pathways that do not include salicylate (18), and catechol 1,2-dioxygenase activity and gentisate 1,2-dioxygenase activity have been detected in fusaria grown on other aromatic substrates (6). Growth on other aromatic compounds.…”
Section: Resultsmentioning
confidence: 99%